RETRACTED: Among Live and Dead Bacteria, the Optimization of Sample Collection and Processing Remains Essential in Recovering Gut Microbiota Components - Bellali, Sara; Lagier, Jean-Christophe; Raoult, Didier; Bou Khalil, Jacques (Frontiers in Microbiology, 2019)
The human gut microbiota plays an important role in human health. Accessing and culturing the gut microbes remains critical in microbiology. The culturomics approach, combined with sequencing strategies, provides new insights in the study of gut microbiota components. However, we are still far from having described all the microbes. Many factors are involved in recovering as much bacteria as possible. One of the most important factors is sample preparation and conservation. The aim of the present work was to evaluate three different types of stool sample conditioning by mainly studying the effect of atmospheric oxygen on bacterial viability and culturability. Quantitative analysis of fecal samples from 8 different healthy individuals was carried out by using a culture-independent method (flow cytometry) and a culture-dependent method (plating technique).We found that the cultured bacteria reached a 50% yield when the samples were exposed to oxygen for 120 minutes without any protectant medium, while the percentage of culturability increased to 67% in the presence of antioxidants. More importantly, when samples were exposed to oxygen less than 2 minutes combined with the work under anaerobic chamber, no discordance was found between the two counting techniques and the culturability increased to 87%. Our study confirmed the importance of sample conditioning to preserve the bacterial viability in samples, especially for oxygen-sensitive intestinal bacteria.